Selenium biofortification of green spinach (Amaranthus spp.) affected by soil types, phosphorus fertilization and selenium sources, and application timing - Nayan, Dayang Safinah (2020)
In selenium (Se) biofortification strategy of green spinach through fertilization, the mechanism or process that affect its availability in soils and uptake by plants is very important to understand. Therefore, in this study, selenite, Se (IV) and selenate, Se (VI) adsorption and desorption in soil type that are commonly grown with vegetables in Malaysia were evaluated. Adsorption-desorption study in soils of various textures was performed with Se concentration from 0-2 mg/L in the form of Se (IV) and Se (VI), respectively. Next, to determine the effect of various species of applied Se on dry matter, Se uptake, and antioxidant activity of green spinach, a glasshouse experiment was conducted in a factorial (2x5) completely randomized design, with two forms of Se (Se (IV) and Se (VI)) and five Se rates (0-60 g Se/ha as soil application in solution form). Then, a factorial (3x4) randomized complete block design experiment was conducted under a glasshouse condition to determine the effect of P on Se accumulation in green spinach. Green spinach was applied with Se (IV) at rates 0-180 g/ha as sodium selenite. Phosphorus fertilizer was applied at 0, 50, and 100% from the recommended amount of 23 kg/ha P2O5. And lastly, a field experiment was conducted in randomized complete block design to evaluate the effect of Se application timing on the dry matter, growth, and Se accumulation in plant. Based on adsorption-desorption study, selenite was adsorbed more (0.02 – 19.25 mg/kg) in all studied soil compared to selenate, (0.01 – 12.39 mg/kg). However, more Se (VI) was desorbed which is between 0 – 100%, as compared to Se (IV) which is only 0 – 66.7%. From glasshouse experiment, Se uptake by leaves was higher when plant was applied with Se (VI) which is 12.58 µg/10 plants as compared to Se (IV), with only 9.01 µg/10 plants. However, higher dry matter and antioxidant activity of green spinach were observed when Se (IV) was applied. In general, Se as Se (IV) has been shown to have more beneficial effect on plant yield, as well as the antioxidant activity in green spinach as compared to Se (VI) and conventionally grown green spinach (0 g/ha Se). Results from this study also show that the highest dry matter was obtained when Se ii was applied at 120 g/ha with 100% of P fertilizer (106 g/10 plants). In leaves and stems, the highest uptake was observed when 120 g/ha Se with 100% of P fertilizer was applied with 23.07 µg/10 plants and 7.40 µg/10 plants, respectively. Applying P fertilizer as recommended could increase yield as well as the Se uptake by leaves and stems of green spinach. Selenium as Se (IV) at 120 g/ha applied to sandy clay soil was considered as the optimum rate as higher rates could reduce plant yield and decrease the Se uptake by green spinach. During the field experiment, plant yield was affected by the Se application timing. In general, single application of Se at 14 DAP gave the best result in terms of growth of the plant during the field experiment. Although the highest Se accumulation in leaves was observed when Se was applied at 7 DAP, the decrease in yield cause it to be regarded as inappropriate time of application.